NeoVax: Smart Child Vaccination and Monitoring Platform - Aishwarya Baba Bankar; Vaishnavi Ajit Nachan; Pallavi Sudhakar Khulpe (International Journal of Children, 2026)
Child vaccination plays a crucial role in preventing life-threatening diseases and ensuring long-term public health. Despite the availability of structured immunization programs, many children miss scheduled vaccinations due to lack of awareness, busy lifestyles of parents and absence of effective reminder systems. This research paper presents NeoVax, a smart and user-friendly child vaccination reminder and management system designed to address these challenges using digital technology.NeoVax is an Application that enables parents to register their child’s vaccination details and receive timely reminders through multiple communication channels such as SMS, WhatsApp and Email. In addition to reminders, the system provides personalized diet recommendations to support the child’s immunity, allows flexible rescheduling of missed vaccinations. The system also integrates basic Machine Learning techniques to predict missed vaccinations and optimize reminder timing.The proposed system aims to improve vaccination compliance, reduce missed doses and enhance parental awareness. By combining automation, personalization and intelligent prediction, NeoVax contributes to improving child healthcare management in both urban and rural settings.One of the most important features of NeoVax is the child vaccination profile. This profile keeps a complete record of every vaccination related to the child. It clearly shows which vaccinations have been done, which ones are still pending, and which ones were missed. Along with this, it also shows the exact dates for each vaccination. Parents can check this information anytime through the system, so they always know the current health status of their child.If a parent misses a vaccination appointment, the system does not simply ignore it. Instead, it automatically reschedules that missed vaccination and updates all future reminders accordingly. This way, no vaccination is permanently skipped, and the child's immunization continues without any break.NeoVax also includes a AI Assistant that works like a helpful assistant for parents. Parents can ask questions about vaccines, side effects, or any general health concerns related to their child. The AI Assistant gives instant and reliable answers, so parents do not have to wait or visit a doctor for basic information. Along with answering questions, the AI Assistant also suggests a proper diet plan based on the child's age. For example,soft food suggestions for toddlers, and balanced meal plans for older children. This helps parents take better care of their child's nutrition alongside vaccination.Overall, NeoVax is built to make child vaccination easy, organized, and stress-free for every parent, whether they live in a city or a rural area.
Keywords: Child Vaccination System; Immunization Management; Machine Learning; Smart Healthcare; digital health; healthcare technology; predictive analytics; reminder system